Effects of frequency on bubble-cloud behavior and ablation efficiency in intrinsic threshold histotripsy. (11th November 2021) - Edsall, Connor; Ham, Emerson; Holmes, Hal; Hall, Timothy L; Vlaisavljevich, Eli
Abstract: Objective. Histotripsy is a non-thermal focused ultrasound ablation method that destroys tissue through the generation of a cavitation bubble cloud. Previous work studying intrinsic threshold histotripsy has shown that dense bubble clouds can be formed by a single-cycle pulse when the negative pressure exceeds an intrinsic threshold of ∼25–30 MPa, with the ablation efficiency dependent upon the size and density of bubbles within the cloud. This work investigates the effects of frequency on bubble-cloud behavior and ablation efficiency in intrinsic threshold histotripsy. Approach. A modular transducer was used to expose agarose tissue phantoms to 500 kHz, 1 MHz, or 3 MHz, histotripsy pulses. Optical imaging was used to measure the bubble-cloud dimensions, bubble density, and bubble size. The effects of frequency on ablation efficiency were also investigated by applying histotripsy to red blood cell (RBC) phantoms. Main results. Results revealed that the bubble-cloud size closely matched theoretical predictions for all frequencies. The bubble density, which is a measure of the number of bubbles per unit area, was shown to increase with increasing frequency while the size of individual bubbles within the cloud decreased at higher frequencies. Finally, RBC phantom experiments showed decreasing ablation efficiency with increasing frequency. Significance. Overall, results demonstrate the effects of frequency on histotripsy bubble-cloud behavior and show that lower frequency generates more efficient tissue ablation, primarily due to enhanced bubble expansion.